Editorial Review Board / Corpo de Avaliadores/ Lista de Evaluadores 2020 - Editor-in-Chief jCEC (The Journal of Engineering and Exact Sciences)
Editorial Review Board / Corpo de Avaliadores/ Lista de Evaluadores 2020